Isolation of oxalotrophic bacteria able to disperse on fungal mycelium. Issue 2 (10th October 2013) - Bravo, Daniel; Cailleau, Guillaume; Bindschedler, Saskia; Simon, Anaele; Job, Daniel; Verrecchia, Eric; Junier, Pilar
Abstract: A technique based on an inverted Petri dish system was developed for the growth and isolation of soil oxalotrophic bacteria able to disperse on fungal mycelia. The method is related to the 'fungal highways' dispersion theory in which mycelial fungal networks allow active movement of bacteria in soil. Quantification of this phenomenon showed that bacterial dispersal occurs preferentially in upper soil horizons. Eight bacteria and one fungal strain were isolated by this method. The oxalotrophic activity of the isolated bacteria was confirmed through calcium oxalate dissolution in solid selective medium. After separation of the bacteria–fungus couple, partial sequencing of the 16S and the ITS1 and ITS2 sequences of the ribosomal RNA genes were used for the identification of bacteria and the associated fungus. The isolated oxalotrophic bacteria included strains related to Stenotrophomonas, Achromobacter, Lysobacter, Pseudomonas, Agrobacterium, Cohnella, and Variovorax . The recovered fungus corresponded to Trichoderma sp. A test carried out to verify bacterial transport in an unsaturated medium showed that all the isolated bacteria were able to migrate on Trichoderma hyphae or glass fibers to re‐colonize an oxalate‐rich medium. The results highlight the importance of fungus‐driven bacterial dispersal to understand the functional role of oxalotrophic bacteria and fungi in soils.